Age-specific associations of RBC folate and several serum folate forms with obesity risk: NHANES 2011–2018 - Wang, Meng; Tong, Zonghang; Li, Chaoxue; Wang, Yanhong; Yang, Xueli; Gong, Zhongying; Zhang, Qiang; Wang, Xuan; Zhang, Xumei (Frontiers in Nutrition, 2025)
BackgroundThis study aims to explore the associations between RBC folate, several serum folate forms [serum total folate, 5-methyltetrahydrofolate (5-mTHF), and unmetabolized folic acid (UMFA)], and obesity risk in middle-aged and older populations.MethodsData from NHANES (2011–2018) included 11,615 participants. Generalized linear models (GLMs) were applied to investigate associations of RBC folate and various serum folate forms with obesity risk after multivariable adjustment. Potential effect modifications were examined through stratified analyses and multiplicative interaction testing.ResultsAmong the total sample, middle-aged, and older participants, 4578 (39.4%), 3613 (40.0%), and 965 (37.2%) were obese, respectively. A positive association between RBC folate and obesity risk was observed, with the highest risks of obesity were consistently found in the fourth quartile (≥ 1,430 nmol/L) for the middle-aged adults (OR = 1.104, 95% CI: 1.045–1.166) and the older participants (OR = 1.157, 95% CI: 1.036–1.293). A significant negative association between serum total folate levels and obesity risk in middle-aged participants, with an OR of 0.804 (95% CI: 0.773–0.835) in the highest quartile (≥ 54.2 nmol/L). Similarly, serum 5-mTHF levels were negatively associated with obesity risk, with an OR of 0.800 (95% CI: 0.772–0.830) in the highest quartile (≥ 51.2 nmol/L). Most importantly, older participants with UMFA levels in the fourth quartile (≥ 1.06 nmol/L) had a higher risk of obesity (OR, 1.056; 95% CI: 1.004–1.110) compared with those with lower UMFA levels, but this association was not found in the total participants or the middle-aged participants.ConclusionSignificant positive relationships exist between RBC folate and obesity risk. Additionally, low serum 5-mTHF in middle-aged participants and high UMFA in older adults were associated with increased obesity risk, highlighting the importance of monitoring folate concentrations for guiding future clinical trials on folate supplementation.